Flow chemistry applied to hazardous reactions, and fluorophores synthesis with photophysics studies - Souza, Juliana Maria de (Universidade Federal de São Carlos, 2020)
Two distinct cases of continuous flow conditions applied to dangerous reactions are described. The first example is the continuous photooxygenation of a series of dienes that produces endoperoxides and / which are potentially explosive intermediates. End-to-end approaches involving endoperoxidation, Kornblum-DeLaMare rearrangement (KDM) and additional hydroxyienone rearrangements are widely described with scope. In the second example, we describe the development of a flow configuration to perform two dangerous steps in the synthesis of Lamivudine (3TC - medicine for HIV / AIDS). The described route is under development by Medicines for All Institute (M4ALL), an American startup from Virginia Commonwealth University (VCU). We have also developed the synthesis of sulfur-ilidenomalonitrile, versatile intermediates in the synthesis of multisubstituted heterocycles (pyridines and pyrones) and amidine-based fluorescent probes.
Química de fluxo aplicada a reações perigosas e síntese de fluoróforos com estudos fotofísicos
Keywords: Flow chemistry; Synthesis; Photooxygenation; Singlet oxygen; Lamivudine; Ylidenemalononitriles; Fluorescence; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA